2022
DOI: 10.1002/cbin.11929
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of markers based on m6A related to prognosis combined with immune invasion of renal clear cell carcinoma

Abstract: The incidence rate of renal cell carcinoma (RCC) is about 3% of all adult cancers. Of these, the Kidney clear cell renal cell carcinoma (KIRC) is the most common type, accounting for about 70%-75% of RCC. KIRC is difficult to be detected in time clinically. KIRC still has no effective treatment at this stage. We combined highthroughput bioinformatics analysis to obtained the structural sequence transcriptome data, relevant clinical information, and m 6 A gene map of KIRC patients from genomics TCGA database. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…LINC02154 increases liver cancer cell growth and spread by increasing SPC24 promoter activity and modulating the PI3K-AKT signaling pathway [28]; it may also be used to estimate the prognosis of laryngeal squamous cell carcinoma [29]. Studies have shown that renal cancer patients with high expression of LINC02154 have a poor prognosis, and knocking down LINC02154 can inhibit the invasion ability of cancer cells, which is consistent with our experimental results [30,31]. IGFL2-AS1 exerts a tumor-promoting effect in TSCC through the Wnt/β-catenin pathway and enhances the development of tongue squamous cell carcinoma [32].…”
Section: Discussionsupporting
confidence: 88%
“…LINC02154 increases liver cancer cell growth and spread by increasing SPC24 promoter activity and modulating the PI3K-AKT signaling pathway [28]; it may also be used to estimate the prognosis of laryngeal squamous cell carcinoma [29]. Studies have shown that renal cancer patients with high expression of LINC02154 have a poor prognosis, and knocking down LINC02154 can inhibit the invasion ability of cancer cells, which is consistent with our experimental results [30,31]. IGFL2-AS1 exerts a tumor-promoting effect in TSCC through the Wnt/β-catenin pathway and enhances the development of tongue squamous cell carcinoma [32].…”
Section: Discussionsupporting
confidence: 88%
“…We investigated the function of identified four m6A and cuproptosis-linked lncRNAs in ccRCC. Given that only LINC02154 and NFE4 expression was upregulated in ccRCC (F i g. 3 I) and that LINC02154 has been described as a cuproptosis-linked gene and well-studied in various carcinomas including ccRCC [ 46 48 ], NFE4 was primarily focused.…”
Section: Resultsmentioning
confidence: 99%
“…The omics-based analytical approaches are becoming available to enhance the understanding of the tumor pathophysiology (15,16). Transcriptomic technique focuses on coding and noncoding sequences to identify differentially expressed genes.…”
Section: Discussionmentioning
confidence: 99%